Reexamining the ideal depth of endotracheal tube in neonates - Hao-Wei Chung; Wei-Te Lee; Hsiu-Lin Chen (Elsevier, 2018)
The appropriate endotracheal tube (ET) depth for the newborn with respiratory failure is important. Inappropriate ET depth increases the risk of uneven lung expansion and collapse. This retrospective study aimed to compare the final ideal ET depth with Tochen's formula in Taiwanese intubated neonates, and to determine the correlation between neonatal factors and final ideal ET depth, and to devise an accurate predictive formula for use in Taiwan. Methods: Data were collected from neonates who required endotracheal intubation and who were admitted to the Neonatal Intensive Care Unit from 2011 to 2015. Correlations between the final ideal ET depth, GA, and BW were assessed using the Pearson correlation test. Multiple regression analysis was used to produce a formula to predict appropriate ET depth from mouth angle to midtracheal position of neonates. Results: A total of 139 neonates were enrolled in this study. The final ideal ET depth was in concordance with Tochen's formula only in 19 neonates (13.7%); relatively deeper in 30 (21.6%) neonates; and shallower than the values from Tochen's formula in 90 (64.7%) neonates. Multiple regression analysis showed that the BW and GA together produced best prediction for final ideal ET depth in our study population. SGA and gender were shown to be insignificantly related to final ideal ET depth. Conclusion: Our study showed the final ideal ET depth was shallower than Tochen's formula in 64.7% of neonates. Tochen's formula might not be suitable to predict ET depth for neonates in Taiwan. In our study, the new formula: 4.0 + 1.0 BW (kg) + 0.05 GA (weeks) provides a more accurate value and alternative method for evaluating the final ideal ET depth in Taiwan. A practical guideline for Asian neonates should be validated by prospective studies with large sample sizes.